Globalization, Spending and Income Inequality in Asia Pacific. Issue Volume 15:Issues 1(2016) (2nd January 2016) - Wong, M.Y.H.
ABSTRACT: This paper provides an overview of the patterns of government spending and income distribution in the Asia-Pacific region under globalization. Previous studies have not placed much emphasis on the underlying policy mechanisms. Not only does this article take the change in public spending into account, it also allows for different factors and distributive outcomes to be associated with distinct types of spending (education, welfare and health). Health-related spending is found to reduce income inequality, while the reverse is true for welfare expenses. The results also suggest that globalization strongly exacerbates income inequality even after controlling for economic, demographic and political factors. The results carry significant implications for governments in the Asia-Pacific region.